Arborização urbana: uma contribuição à qualidade de vida com uso de geotecnologias - Schuch, Mara Ione Sarturi (2006)
Street arborization can influence directly population s life quality because it can offer some benefits such as: thermal comfort, shade, reduction of pollution and noise. These benefits can contribute to the physical-environmental equilibrium of cities. However, lack of urban planning in the implementation and maintenance of street arborization can influence its efficiency. In this sense, the objective of this research is two-fold: analyze the street arborization in the central area of São Pedro do Sul, RS, and elaborate a proposal to reorder the urban scenario. In order to do that, the methodology was divided in five steps: firstly, urban components were identified electrical energy transmission system, water distribution system, sewer system, light and telephone poles, public telephones, street signs, trees and streets through field work and map analysis. Secondly, quali-quantitative aspects of arboreal species were identified observing its location, the relation with the urban components and the phytosanitary conditions through field work. Thirdly, thematic maps for the urban components were elaborated through Digital Cartography, using the software SAGA (Sistema de Análise Geo-Ambiental), and Geoprocessing, using SIG (Geographic Information System). Fourthly, some arboreal species were identified and characterized as adequate for street and park s arborization. As the last step, a questionnaire was applied to evaluate population s environmental perception. The results of the research indicate that the 415 trees registered are from 49 different species: 5 species represent 67,5% of those trees and 44 species represent 32,5%. Some suggestions were given for the introduction of new species and substitution of old ones to improve population s life quality